Potential Development of Agriculture Commodity High Economy Value in Daerah Istimewa Yogyakarta Province - SUBOWO GITOSUWONDO (Jurnal Sumberdaya Lahan, 2009)
Indonesia has been able to reach self sufficiency for rice, but the problem is decreasing farmer economic value exchange. For that reason besides pursuing increase land productivity and agriculture commodities development, the improvement farmer income must be done. Daerah Istimewa Yogyakarta Province has ± 0,319 million ha within land typology from mountainous vulcanize until sand shore. The problem is narrow land tenure, so that to increase farmer income the development of agriculture commodity with high economics value should be executed based on land carrying capacity. High diversity of land typology with good irrigation network and farm road infrastructure make DI Yogyakarta Province potential to be developed as agriculture seed centre and off season commodity planting. The minerals deposit of volcanous Merapi mountain and marine can increase quality ofagricultural product which good for health, therefore it is potential for development of functional food and improvement livestock reproduction for calf production. Through agricultural product that has high economics value, farmer income and public prosperity are expected to increased.